Răspuns :
a = I nr
6a = II nr
a - 173 = III nr
a + 6a + a - 173 = 2011
8a = 2011 +173
8a = 2184
a = 2184 : 8
a = 273
I nr = 273
II nr = 273 x 6 = 1638
III nr = 273 - 173 = 100
273 + 1638 + 100 = 2011
6a = II nr
a - 173 = III nr
a + 6a + a - 173 = 2011
8a = 2011 +173
8a = 2184
a = 2184 : 8
a = 273
I nr = 273
II nr = 273 x 6 = 1638
III nr = 273 - 173 = 100
273 + 1638 + 100 = 2011
a,b,c numerele
a+b+c=2011
a=b:6
b=6a
c=a-173
înlocuind in suma
a+6a+a-173=20116
8a=2011+173
8a=2184
a=2184:8
a=273
b=6×273
b=1638
c=273-173
c=100
P:100+1638+273=2011
a+b+c=2011
a=b:6
b=6a
c=a-173
înlocuind in suma
a+6a+a-173=20116
8a=2011+173
8a=2184
a=2184:8
a=273
b=6×273
b=1638
c=273-173
c=100
P:100+1638+273=2011